Effect of Egg Size on Fertility and Hatchability in Betong Chickens - Boonthep, Kettawan; Angkuraseranee, Talerngsak; Chansri, Pairat (YRU Journal of Science and Technology, 2025)
Hatching rate and chick quality are important problems in chick production. That depends on many factors. The factors before hatching are breed, health nutrient and age of the parents. Another factor is the condition of the egg such as egg size and its weight. This study aimed to evaluate the effect of egg size on fertility and hatchability in Betong chickens. A total of 150 female Betong chickens, aged six months, were individually housed throughout the fertile period. Each bird was provided with 80 grams of commercially available rooster breeder feed per day (protein content > 20%). Twenty adults male Betong chickens, aged one year, were used for semen collection, with inseminations performed three times per week. The study was conducted using a randomized complete block design (RCBD). Egg production was categorized into three groups based on egg weight: G1 (40–45 grams), G2 (46–50 grams), and G3 (51–55 grams). Eggs were incubated weekly, and fertility was assessed by candling on days 7 and 18 of incubation. Egg weight was measured on days 1, 7 and 18. The results indicated that Betong chickens produced an average of 12.03 ± 0.51 eggs per bird per month, leading to a cumulative annual average of 144.34 eggs/bird. The average egg weight was 48.08 grams. Although the effect of egg size on hatchability was not statistically significant (P>0.05), higher hatchability rates were observed in the G2 and G3 groups (89.47% and 89.27%, respectively). The percentage of egg weight loss in the G3 group (6.64%) was the highest, the chick weight (34.37 g) was significantly higher than that of the G1 and G2 groups (28.67 and 30.53 g) (P<0.05). Therefore, selecting medium-sized eggs may result in larger chicks, which could increase hatchability rates and positively impact the viability of Betong chicks.